The chronic effects of concussion on gait. Issue 4 (27th March 2011) - Martini, D; Sabin, M; Depesa, S; Leal, E; Negrete, T; Sosnoff, J; Broglio, S
Abstract : Background: Concussion has a clear effect on motor control with acute alterations in gait documented up to 30 days post injury. These changes include increased stance time and decreased velocity. It is unknown if alterations persist beyond one month post-injury. Objective: To evaluate the chronic effects of concussion on gait in individuals with and without an injury history. Design: A cross-sectional study. Setting: A laboratory setting. Participants: 68 individuals ages 18–35 years (37 males, 20.8±1.9 years, 171.0±9.8 cm, 74.5±14.8 kg) were divided in two groups based on self-report of previous concussion history (zero (n=40) and one or more (n=28, 2.0±1.4 previous concussions, 6.3±4.1 years prior)). Interventions: All participants completed a gait assessment during four conditions: unobstructed (Con1) and obstructed (Con3) walking without a cognitive task; and unobstructed (Con2) and obstructed (Con4) walking with a cognitive task. The cognitive task was a modified Brooks Spatial Task, requiring the recall of digits one through eight in a four-by-four matrix. Obstructed walking involved stepping over two 29.5 cm blocks that divided the walkway into thirds. Main outcome measures: Gait velocity and percent time in single limb stance (SLS%) and double limb stance (DLS%) were evaluated with multiple mixed model analyses of variance (group (2) x condition (4)) with repeated measures on condition. Results: Previously concussed individuals walked slower in during Con1 (p=0.02). Significant group effects were seen for SLS% and DLS%. The concussed group demonstrated significantly shorter SLS% during Con3 (p<0.000) and Con4 (p=0.001). Similarly the concussed group had significantly longer DLS% during Con1 (p=0.003), Con3 (p=0.001), and Con4 (p=0.001). Conclusion: Our findings indicate that individuals reporting a previous history of concussion adopt a slower and more stable/conservative gait strategy than our non-concussed controls.